Effects Of Pesticides On Environment And Human Health - Dr.Balraj Singh,Dr.AshutoshAwasthi, Mr. Devendra Pal Singh (International Journal of Modern Agriculture, 2021)
Chemical stress on natural environments has increased in agricultural industrial development. Pesticides are agrochemicals used for the protection in agricultural, ecological and industrial green spaces of plants and people from various pathogens. Furthermore, their recorded potential for producing a significant detrimental effect on security and the weather can be a serious factor of their side effects on environmental health dangers. There are many ground-breaking conceptual modifications in agriculture and in food processing, which have incorporated productive practise leading to food Sovereignty and are the compelling need for further effective and environmentally responsible solutions. It is clearer than ever that society wants to adopt a modern agricultural model for food production that is healthier for environments and human beings. It has become important to add industrial fertilizers and pesticides for optimal output of agricultural produce and to feed the increasing population. These types of farming practices have allowed food grain growth and sustainability but at the same time have a significant effect on the human health and environment. This paper offers a description of the public safety and environmental effects of agricultural pesticides and fertilizers.